Dynamics of Silicon Valley civilization in the Globalization - Hapuarachchi, Ajantha (My University, 2006)
In this Paper I have tried answering some of the questions that also would define- what is Silicon Valley civilization? And why we called it a Civilization? This paper also deals with how Silicon Valley Civilization has influenced every walk of life, particularly Education, Language, Media Technology, Religion, Gender, and Science. Globalization in terms of its definition is mostly connected with commerce, media and communication technology that have helped the world to shrink its virtual size. Proved by the civilizations found in Mesopotamia, Babylonia, and Indus-Valleys, our species have come a long way in the industrial revolution. Silicon Valley is the birthplace of all the modern technology, which has augmented the otherwise slow paced process of globalization. We are now representing the Silicon Era, which has evolved through electric, electronic and information Eras. All these were possible only because of the communication skills and its development, the human achieved over a period of time. Silicon Valley Civilization in all about communication and exchange of ideas. All these ages we mentioned earlier came into being with special inventions. The invention of the Computer was the major discovery in the history. Digital computer cleared the path for development of technological sides of all areas under discussion. Digital era or Cyber era started with the revolutionary discovery of computer. Computer has almost replaced human involvement in many of the works, and made life easier. Computer and the WWW enabled humans to communicate and connect to people within seconds, who are far located. 3 The civilization that has grown and matured in a short period of time ,which I would like refer as “Silicon Valley civilization”, is a legendary leap in the history of human, shrinking time and space considerably. As Joshep Dionne, 1987 , explains “The industrial revolution changed the way we work in two centuries. The information revolution has done as much as in two decades” If we consider education, culture, religion, social life, media technology, and science as parameters of civilization, which are the results of human cognitive power and creativity, the computer technology has revolutionized the dimensions of these areas. In this paper the author wish to consider Education, Health, Language, and Religion, with special reference to Media technology within the Silicon society, which are the basic elements of civilization that help socialization from generation to generation .I would also like to pay reader‟s attention towards the Genetic engineering happening in this new Era than the changes of ecological dimension, political, neo-liberalism, geographical, ethical, environmental or other issues related to globalization. This paper contains two parts (a) explanations of “Civilization” and (b) impact of IT in “Globalization” with regard to the above-mentioned areas. Major objective of this paper is to make the reader think in different angle on the concept of Silicon Valley civilization and to focus on this civilization as a reason for generating all the progressive and developmental changes happened to the modern society.